How to avoid interfering electrochemical reactions in ESI‐MS analysis. (11th April 2019) - Lübbert, Christian; Peukert, Wolfgang
Abstract : Electrospray ionization is one of the pillars of modern mass spectrometry. The presence of electrochemical reactions occurring in an electrospray processes results in oxidation or reduction of either electrolyte species in the liquid sprayed or of the electrode material in contact with the liquid resulting in the generation of new chemical species. These reactions can substantially alter the analytes such that the ions observed in the gas phase have a different mass and/or charge than the species originally in the solution and the identification of species may get quite challenging. In this perspective special feature article, Christian Lübbert and Wolfgang Peukert present a simple and robust electrospray ion source concept involving an electrically isolated sample feed system and flow splitting. The setup allows for enduring electrospray operation unaffected by electrochemical reactions. Further, it can be used as a reference setup for the investigation of electrochemical reactions occurring in electrospray emitters. Prof. Dr.‐Ing. Wolfgang Peukert is head of the Institute of Mechanical Process Engineering at the Friedrich‐Alexander‐University Erlangen‐Nuremberg (Germany). The long‐term goals of the institute ranges from a molecular understanding of particle surfaces and interfaces, to methods of particle production and processing.